Building new hotel brand reputation to attract guest in Semarang city - Wijaya, Muhammad Askha Rafliansyach; Handoyo, Siaw Armando; Asshofi, Izza Ulumuddin Ahmad (Surya Hijau Manfaat, 2024)
The hotel industry is an industry that plays an important role in the development of the economy and tourism in Indonesia. The research aims to elaborate brand reputation for new hotels in Semarang. This article uses descriptive research using descriptive qualitative research methods assisted by data collection through documentation and literature study. The research will be conducted using AIDA theory on the 5 newest hotels built in the last 3 years in the city of Semarang. The results show that an increasing of guests in numbers. with the help of AIDA theory, and comparison, it shows that we can still be able to save the hotel industry so that it will not perish that the Room Occupancy Rate (ROR) of star-rated hotels in semarang city for the November 2021 period was recorded at 60.25 percent or an increase of 4.12 points compared to October 2022, which was influenced by the increase in ROR that occurred in the class of 2-star, 3-star, 4-star and 5-star hotels (BPS, 2023). It can be concluded that the ratings that guests give to hotels have good feedback such as good and friendly service, comfortable rooms, strategic hotel location. New hotel gain market awareness due to the needs of customer especially in this recent time. Due to an increasing of numbers in covid cases, and with many new hotels, it shows the interest of hospitality industry. Hotel must do more to promote and get more customers.